The General Commissariat of Cults in the Republican Zone in the Spanish Civil War (1938-1939) - Ginard Féron, David (Hispania Nova, 2024)
In the final period of the Spanish Civil War, the government of Juan Negrín decided to reestablish public Catholic worship in the republican zone. For this purpose, a General Commissariat of Cults was established, headed by the Catalan doctor Jesús Maria Bellido Golferich. As a measure closely linked to the strategy of democratic normalization formulated in the spring of 1938 in the so-called “thirteen points” of the Negrín government, this turn in republican religious policy generated relatively abundant reactions in the media of the two contending areas and abroad. This work addresses the origins of the Commissariat, as well as its fleeting activity (December 1938-January 1939), in the context of the dispute over national and international public opinion between Republicans and Francoists.
Keywords: secularism; clericalism; Catholic worship; Second Spanish Republic; Spanish Civil War